Graphene related materials for thermal management. (22nd October 2019) - Fu, Yifeng; Hansson, Josef; Liu, Ya; Chen, Shujing; Zehri, Abdelhafid; Samani, Majid Kabiri; Wang, Nan; Ni, Yuxiang; Zhang, Yan; Zhang, Zhi-Bin; Wang, Qianlong; Li, Mengxiong; et al.
Abstract: Almost 15 years have gone ever since the discovery of graphene as a single atom layer. Numerous papers have been published to demonstrate its high electron mobility, excellent thermal and mechanical as well as optical properties. We have recently seen more and more applications towards using graphene in commercial products. This paper is an attempt to review and summarize the current status of the research of the thermal properties of graphene and other 2D based materials including the manufacturing and characterization techniques and their applications, especially in electronics and power modules. It is obvious from the review that graphene has penetrated the market and gets more and more applications in commercial electronics thermal management context. In the paper, we also made a critical analysis of how mature the manufacturing processes are; what are the accuracies and challenges with the various characterization techniques and what are the remaining questions and issues left before we see further more applications in this exciting and fascinating field.